Mice lacking PLAP-1/asporin counteracts high fat diet-induced metabolic disorder and alveolar bone loss by controlling adipose tissue expansion - Hiromi Sakashita (Nature Portfolio, 2021)
Abstract Adipose tissue fibrosis with chronic inflammation is a hallmark of obesity-related metabolic disorders, and the role of proteoglycans in developing adipose tissue fibrosis is of interest. Periodontal disease is associated with obesity; however, the underlying molecular mechanisms remain unclear. Here we investigated the roles of periodontal ligament associated protein-1 (PLAP-1)/asporin, a proteoglycan preferentially and highly expressed in the periodontal ligament, in obesity-related adipose tissue dysfunction and adipocyte differentiation. It was found that PLAP-1 is also highly expressed in white adipose tissues. Plap-1 knock-out mice counteracted obesity and alveolar bone resorption induced by a high-fat diet. Plap-1 knock-down in 3T3-L1 cells resulted in less lipid accumulation, and recombinant PLAP-1 enhanced lipid accumulation in 3T3-L1 cells. In addition, it was found that primary preadipocytes isolated from Plap-1 knock-out mice showed lesser lipid accumulation than the wild-type (WT) mice. Furthermore, the stromal vascular fraction of Plap-1 knock-out mice showed different extracellular matrix gene expression patterns compared to WT. These findings demonstrate that PLAP-1 enhances adipogenesis and could be a key molecule in understanding the association between periodontal disease and obesity-related metabolic disorders.